Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1111/j.1744-7348.2002.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cercospora zeae‐maydis infested maize residue on progress and spread of grey leaf spot of maize in central Uganda

Abstract: The spread of grey leaf spot caused by Cercospora zeae-maydis from infested maize residue on the soil surface and progress over time were studied under tropical conditions at two locations in central Uganda, Kabanyolo and Namulonge, using a susceptible local cultivar, LP16. Infested maize residue collected the previous season was used as the inoculum source in varying amounts; 80% coverage, 40% coverage and 0% soil coverage were used to simulate no tillage, minimum tillage and maximum tillage with complete bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Several studies examining rust dispersal in crop canopies have been undertaken. However, sources of inoculum for these studies have most often contained enough propagules to form several, in some cases several thousand, initial infections on individual plants (Willocquet et al ., ), on several plants within a focal area (Asea et al ., ; Sackett & Mundt, ), or on entire fields (Gitaitis et al ., ). More recently, it was demonstrated that the highly local dissemination of wheat leaf rust requires the study of individual lesions if the full epidemiological impacts of dispersal gradients are to be understood (Lannou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examining rust dispersal in crop canopies have been undertaken. However, sources of inoculum for these studies have most often contained enough propagules to form several, in some cases several thousand, initial infections on individual plants (Willocquet et al ., ), on several plants within a focal area (Asea et al ., ; Sackett & Mundt, ), or on entire fields (Gitaitis et al ., ). More recently, it was demonstrated that the highly local dissemination of wheat leaf rust requires the study of individual lesions if the full epidemiological impacts of dispersal gradients are to be understood (Lannou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The infected residue of a previous crop left over the soil surface is the principal source of inoculums. There was a strong positive correlation between the amount of infected maize residue and disease inoculums (Asea et al, 2002;de Nazareno et al, 1993a). They reported that disease intensity was higher in a high residue treated plot than a non treated plot.…”
Section: Residues and Weed Managementmentioning
confidence: 98%
“…The major foliar diseases of economic importance in the mid‐altitude and highland ecologies of ESA are northern corn leaf blight (NCLB) caused by Exserohilum turcicum (Pass.) Leonard & Suggs (Pratt et al., 2003; Vivek et al., 2010), gray leaf spot (GLS) caused by Cercospora zeae‐maydis Tehon & Daniels (Asea et al., 2002; Bigirwa, Pratt, Adipala, & Lipps, 2001; Menkir & Ayodele, 2005; Ward, Stromberg, Nowell, & Nutter, 1999), and common rust caused by Puccinia sorghi Schwein (CABI, 2019; Fininsa & Yuen, 2001; Vivek et al., 2010).…”
Section: Introductionmentioning
confidence: 99%